DECODING ECONOMIC GROWTH: ENDOGENOUS PERSPECTIVES ON CAMEROON'S LONG-TERM TRAJECTORY - Williams, Dr. Rachel M.; Davis, Prof. Jonathan K.; Bennett, Dr. Emily C. (International Journal of Allied Research in Economics (IJARE), 2024)
This study investigates the determinants of economic growth in Cameroon through the lens of the recent endogenous growth theory, as pioneered by Romer (1986) and Lucas (1988). Unlike the traditional Solow-Swan neoclassical model, which posits that long-term growth is driven solely by exogenous technical progress and is impervious to policy changes, the endogenous growth theory contends that economic growth is significantly influenced by economic policy decisions. The focal point of this analysis is to discern the role of economic policy in shaping the economic trajectory of Cameroon. The theoretical framework underscores a departure from the conventional wisdom of the Solow-Swan model and posits that the effectiveness of economic policy is a pivotal factor in determining economic growth. The study aims to assess the extent to which economic policy contributes to output growth, acknowledging the nuanced dynamics introduced by the endogenous growth perspective. Economic policy, within this paradigm, is not merely a passive variable but an active determinant that can shape the growth trajectory of a nation. This research places a specific emphasis on country-specific features, particularly within the context of Africa. In the African landscape, economic growth has exhibited a notable degree of instability that cannot be fully explained by inherent country characteristics alone. The investigation seeks to unravel the intricate interplay between economic policy and these unique country-specific features, shedding light on the nuanced nature of growth within the African context. Drawing on insights from Easterly (1993), the study recognizes that understanding economic growth in Cameroon necessitates a tailored analysis that goes beyond generic frameworks. Easterly's findings underscore the importance of recognizing the instability of growth within the African continent and the need for context-specific examinations. By incorporating these insights, the research aims to provide a more comprehensive understanding of the determinants of economic growth in Cameroon. In order to achieve these objectives, the study employs a theoretical foundation rooted in the endogenous growth theory and a methodological approach that involves empirical analyses. The investigation considers various economic policy variables, such as fiscal and monetary policies, trade policies, and institutional factors, to unravel the specific mechanisms through which policy decisions influence economic growth in Cameroon. In conclusion, this research contributes to the economic literature by offering a nuanced perspective on the determinants of economic growth in Cameroon. By embracing the endogenous growth theory, the study goes beyond the traditional paradigms, recognizing the active role of economic policy in shaping long-term growth. The findings are expected to provide valuable insights for policymakers, economists, and stakeholders interested in fostering sustainable economic development in Cameroon.